Arginine-164-tryptophan substitution in connexin32 associated with X linked dominant Charcot-Marie-Tooth disease. Issue 5 (May 1996) - Oterino, A; Montón, F I; Cabrera, V M; Pinto, F; Gonzalez, A; Lavilla, N R
Abstract : A Spanish family with X linked dominant Charcot-Marie-Tooth (CMTX1) neuropathy was screened for point mutations in the connexin32 gene (GJ beta 1). The patients showed a C-T transition at position 552 which predicts arginine to tryptophan substitution at amino acid 164 (R164K). This mutation destroys an AciI restriction site at position 552 and creates a PflMI restriction site.